Langmuir and Freundlich Isotherm Approximation on Adsorption Mechanism of Chrome Waste by Using Tofu Dregs - Dyah Suci Perwitasari; Yahya Ardian Yuma Pracesa; Muhammad Aji Pangestu; Pardi Sampe Tola (Nusantara Science and Technology Proceedings)
The requirement to discover low-cost and high-efficiency adsorbents material for the heavy metal removal of industrial effluents has been growing attention for many environmental researchers. Natural materials are being studied intensively as adsorbent materials because of their abundant source, low-cost processing, and relatively high adsorption efficiency. This study investigates the tofu dregs as adsorbents material to remove chrome metal, the main element in tannery liquid waste. Analysis of experimental data from adsorption processes is crucial to understand and predict removal mechanisms, efficiency, or required adsorbent mass under given initial conditions. Langmuir and Freundlich's adsorption isotherms were applied to the experimental data to determine their intrinsic parameters. The intrinsic parameters of Langmuir and Freundlich adsorption isotherms can subsequently be used to analyze the adsorption mechanism. This was achieved by combining the isotherms equation with mass conservation of solute before and after adsorption